SPEECH CONTEST TO IMPROVE STUDENTS’ FLUENCY IN SPEAKING - Rizky Lutviana (JURNAL ILMIAH BAHASA DAN SASTRA, 2016)
This study is aimed at implementing speech contest to improve students’ fluency in speaking. The subject of this research was 15 students of intermediate level of speaking class. The preliminary study indicated that fluency was students’ problem in speaking since they tended to produce incomplete sentences with many pauses in performing speaking task. The instruments used to collect the data were test, questionnaire and interview. This technique was a real world speaking task in which it required students to deliver speech on a stage in front of audiences individually. The analytical scoring rubric with four criteria, including fluency, accuracy, content, and method of delivery, was used by three raters to determine students’ score. This technique was successfully done in 1 cycle since it met the criteria of success, that was 80% students (12 students), got score 80 or above and 84% students (13 students) showed positive response toward speech contest. Speech contest helped students to show their potential and directed students to work hard eliminating their negative feelings that might hinder their confidence to speak fluently.